2005
DOI: 10.1113/jphysiol.2005.086595
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic synapses as archives of synaptic history: state‐dependent redistribution of synaptic efficacy in the rat hippocampal CA1

Abstract: Plastic modifications of synaptic strength are putative mechanisms underlying information processing in the brain, including memory storage, signal integration and filtering. Here we describe a dynamic interplay between short-term and long-term synaptic plasticity. At rat hippocampal CA1 synapses, induction of both long-term potentiation (LTP) and depression (LTD) was accompanied by changes in the profile of short-term plasticity, termed redistribution of synaptic efficacy (RSE). RSE was presynaptically expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
1
14
0
1
Order By: Relevance
“…Synaptic strength and plasticity have been studied in other central synapses such as CA1 in the rat hippocampus, in which it was shown that the size of PSDs increases in response to pharmacological blockade of spike activity (e.g., Murthy et al,2001; Qin et al,2001; Yasui et al,2005). Quiescent synapses exhibited larger PSDs and increased numbers of SVs, and were accompanied by increases in synaptic strength.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic strength and plasticity have been studied in other central synapses such as CA1 in the rat hippocampus, in which it was shown that the size of PSDs increases in response to pharmacological blockade of spike activity (e.g., Murthy et al,2001; Qin et al,2001; Yasui et al,2005). Quiescent synapses exhibited larger PSDs and increased numbers of SVs, and were accompanied by increases in synaptic strength.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an increase in the number or single channel conductance of α-amino-3-hydroxy-5-methyl-4-isoxolepropionic acid receptors (AMPARs) can be expected to result in a linear scaling of synaptic responses during bursts of activity. There is evidence that each of these mechanisms can account for potentiation (Markram & Tsodyks, 1996; Tsodyks & Markram, 1997; Pananceau, Chen & Gustafsson, 1998; Selig, Nicoll & Malenka, 1999; Yasui et al, 2005). However, no single mechanism has been universally accepted and with few exceptions the entire LTP process has been assumed to result from a single mode of expression (Gustafsson et al, 1989; Gustafsson & Wigstrom, 1990; Hanse & Gustafsson, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, synaptic activation at low frequency mimics poorly the natural patterns of neuronal communication in the hippocampus, as neurons typically communicate with brief high frequency bursts of action potentials (Dobrunz & Stevens, 1999). Indeed, it has been shown that synaptic responses to high frequency bursts of the presynaptic action potentials are not always equally potentiated during LTP (Markram & Tsodyks, 1996; Yasui et al, 2005), although sometimes they are (Pananceau, Chen & Gustafsson, 1998; Selig, Nicoll & Malenka, 1999). Consequently, the functional implications of the long-lasting changes in synaptic transmission cannot be predicted by analyses of the single synaptic responses alone (Markram & Tsodyks, 1996; Tsodyks & Markram, 1997; Dobrunz & Stevens, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…LTD and LTP are long‐term changes in synaptic efficacy that constitute one of the cellular models for information storage. In addition, depotentiation and de‐depression represent another level of plasticity and can alter past synaptic information processing 29. Previous studies have suggested that aberrant depotentiation may lead to the development of abnormal motor patterns 6.…”
Section: Resultsmentioning
confidence: 99%